2010
DOI: 10.1112/jlms/jdq052
|View full text |Cite
|
Sign up to set email alerts
|

The radial masa in a free group factor is maximal injective

Abstract: The radial (or Laplacian) masa in a free group factor is the abelian von Neumann algebra generated by the sum of the generators (of the free group) and their inverses. The main result of this paper is that the radial masa is a maximal injective von Neumann subalgebra of a free group factor. We also investigate the tensor products of maximal injective algebras. Given two inclusions B i ⊂ Mi of type I von Neumann algebras in finite von Neumann algebras such that each B i is maximal injective in Mi, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…and since ε is arbitrary, (iv) is an easy consequence of this. So it is enough to prove (5). Let T ∈ (π 1 ⊕ π 2 )(A) ′ , by the Double Commutant Theorem it is enough to show that…”
Section: Definition Of 1-bounded Entropy and Some Technical Lemmasmentioning
confidence: 96%
“…and since ε is arbitrary, (iv) is an easy consequence of this. So it is enough to prove (5). Let T ∈ (π 1 ⊕ π 2 )(A) ′ , by the Double Commutant Theorem it is enough to show that…”
Section: Definition Of 1-bounded Entropy and Some Technical Lemmasmentioning
confidence: 96%
“…In [CFRW10], it is proved that the subalgebra of the free group factor generated by the symmetric laplacian operator (the radial subalgebra) is maximal amenable. In [Ho14], C. Houdayer provided uncountably many non-isomorphic examples of abelian maximal amenable subalgebras in II 1 -factors.…”
Section: Introductionmentioning
confidence: 99%
“…He defined the notion of asymptotic orthogonality property (AOP) and showed that a singular maximal abelian subalgebra (masa) with the AOP is maximal amenable. Many other examples have been given using the same strategy [Ge96,She06,CFRW10,Bro14,Hou14a,BCa]. A completely new strategy in proving maximal amenability has been given in [BCb].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%